Constraining provenance, thickness and erosion of nappes using low‐temperature thermochronology: the Northland Allochthon, New Zealand. (30th December 2015) - Jiao, Ruohong; Seward, Diane; Little, Timothy A.; Herman, Frédéric; Kohn, Barry P.
Abstract: The Northland Allochthon, an assemblage of Cretaceous–Oligocene sedimentary rocks, was emplaced during the Late Oligocene–earliest Miocene, onto the in situ Mesozoic and early Cenozoic rocks (predominantly Late Eocene–earliest Miocene) in northwestern New Zealand. Using low‐temperature thermochronology, we investigate the sedimentary provenance, burial and erosion histories of the rocks from both the hanging and footwalls of the allochthon. In central Northland (Parua Bay), both the overlying allochthon and underlying Early Miocene autochthon yield detrital zircon and partially reset apatite fission‐track ages that were sourced from the local Jurassic terrane and perhaps Late Cretaceous volcanics; the autochthon contains, additionally, material sourced from Oligocene volcanics. Thermal history modelling indicates that the lower part of the allochthon together with the autochthon was heated to ca . 55–100°C during the Late Oligocene and Early Miocene, most likely due to the burial beneath the overlying nappe sequences. From the Mesozoic basement exposed in eastern Northland, we obtained zircon fission‐track ages tightly bracketed between 153 and 149 Ma; the apatite fission‐track ages on the other hand, generally young towards the northwest, from 129 to 20.9 Ma. Basement thermochronological ages are inverted to simulate the emplacement and later erosion of the Northland Allochthon, using a thermo‐kinematic model coupled with an inversion algorithm. The results suggest that during the Late Oligocene, the nappes in eastern Northland ranged from ca . 4–6‐km thick in the north to zero in the Auckland region (over a distance >200 km). Following the allochthon emplacement, eastern Northland was uplifted and unroofed during the Early Miocene for a period of ca . 1–6 Myr at the rate of 0.1–0.8 km/Myr, leading to rapid erosion of the nappes. Since Middle Miocene, the basement uplift ceased and the erosion of the nappes and the region as a whole slowed down ( ca . 0–0.2 km/Myr), implying a decay in the tectonic activity in this region.